Head of the penitentiary institutions: the issue of legal consolidation of the requirements of professional competence - Zlyvko, Stanislav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article deals with the professional competence and managerial role of the leader in the field of execution of punishment. The main features of the professional competence of the leader in the conditions of the reform of the criminal-executive service are developed. Taking into account the specifics of the appointment and needs of the head of the penitentiary system, the main positions regarding his professional competence are determined.